Implementasi Nilai-Nilai Pancasila dalam Pembelajaran PKN di Madrasah Ibtidaiyah: Studi Literatur - Mamat Rahmat; Elis Ashpiati; Ihsan; Fuji Lestari; Siti Sarah Nurfadilah; Evi Mulyati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of Pancasila values in Civics Education learning at the Madrasah Ibtidaiyah level through a qualitative library research approach. The findings indicate that the integration of Pancasila values in Civics learning remains predominantly normative and cognitively oriented, limiting deeper value internalization among students. Conceptually, value integration occurs through both explicit and implicit approaches, with the latter demonstrating greater effectiveness in fostering reflective and contextual character formation. Pedagogically, participatory, experiential, and value-based learning strategies are found to enhance students’ engagement and support meaningful learning processes. However, structural and contextual challenges, including technological disruption, limited resources, and evolving social dynamics, continue to affect implementation. The study highlights the need for a comprehensive pedagogical framework that integrates value-oriented design, teacher modeling, and adaptive learning environments to strengthen character education. This research contributes to the theoretical development of value-based civic education and offers practical implications for improving instructional practices in Islamic elementary education.